Temperature-Responsive Magnetic Nanoparticles for Bioanalysis of Lysozyme in Urine Samples - Marwa A. Ahmed (MDPI AG, 2021)
Highly selective multifunctional magnetic nanoparticles containing a thermoresponsive polymer shell were developed and used in the sample pretreatment of urine for the assessment of lysozymuria in leukemia patients. Crosslinked poly(N-isopropylacrylamide-co-acrylic acid-co-N-tert-butylacrylamide) was grown onto silica-coated magnetic nanoparticles by reversible addition fragmentation chain transfer (RAFT) polymerization. The lysozyme binding property of the nanoparticles was investigated as a function of time, protein concentration, pH, ionic strength and temperature and their selectivity was assessed against other proteins. High-abundant proteins, like human serum albumin and γ-globulins did not interfere with the binding of lysozyme even at elevated concentrations characteristic of proteinuria. A sample cleanup procedure for urine samples has been developed utilizing the thermocontrollable protein binding ability of the nanoparticles. Method validation was carried out according to current bioanalytical method validation guidelines. The method was highly selective, and the calibration was linear in the 25 to 1000 µg/mL concentration range, relevant in the diagnosis of monocytic and myelomonocytic leukemia. Intra- and inter-day precision values ranged from 2.24 to 8.20% and 1.08 to 5.04%, respectively. Intra-day accuracies were between 89.9 and 117.6%, while inter-day accuracies were in the 88.8 to 111.0% range. The average recovery was 94.1 ± 8.1%. Analysis of unknown urine samples in comparison with a well-established reference method revealed very good correlation between the results, indicating that the new nanoparticle-based method has high potential in the diagnosis of lysozymuria.